2019
DOI: 10.1371/journal.pone.0219405
|View full text |Cite|
|
Sign up to set email alerts
|

Dendritic cells mediate the anti-inflammatory action of omega-3 long-chain polyunsaturated fatty acids in experimental autoimmune uveitis

Abstract: We previously showed that dietary omega (ω)–3 long-chain polyunsaturated fatty acids (LCPUFAs) suppress inflammation in mice with experimental autoimmune uveitis (EAU). We have now investigated the role of antigen presenting cells (APCs) in this action of ω-3 LCPUFAs. C57BL/6 mice were fed a diet supplemented with ω-3 or ω-6 LCPUFAs for 2 weeks, after which splenocytes were isolated from the mice and cocultured with CD4 + T cells isolated from mice with EAU induced by injection of a huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Observed effect is mediated by reduced Th1-inducing (CD11c + CD11b − CD8α + ) lymphoid DCs and increased tolerogenic, myeloid (CD11c + CD11b + CD8α − ) DCs subpopulations [112,113]. In vivo anti-inflammatory actions of dietary n-3 PUFAs are also shown as the inhibition of T cell proliferation and the production of IFN-γ and IL-17 [114].…”
Section: Dendritic Cellsmentioning
confidence: 97%
“…Observed effect is mediated by reduced Th1-inducing (CD11c + CD11b − CD8α + ) lymphoid DCs and increased tolerogenic, myeloid (CD11c + CD11b + CD8α − ) DCs subpopulations [112,113]. In vivo anti-inflammatory actions of dietary n-3 PUFAs are also shown as the inhibition of T cell proliferation and the production of IFN-γ and IL-17 [114].…”
Section: Dendritic Cellsmentioning
confidence: 97%
“…Transfer of dendritic cells from mice fed omega-3 long-chain PUFA diet to mice with EAU decreased the T cell proliferation and the production of IFN-γ and IL-17 by T cells, mitigating the disease development. Splenocytes were isolated from the mice and cocultured with CD4 + T cells isolated from mice with EAU [ 137 ]. Omega-3 long-chain PUFA seem to have a molecular target in T cells, the T-bet and RORγt, Th1- and Th17-related transcription factors, respectively.…”
Section: Inflammation and Fatty Acidsmentioning
confidence: 99%
“…In a previous study, conducted by the authors of the present review, we found that mouse spleen-derived DCs mediate the anti-inflammatory action of dietary ω-3 long-chain polyunsaturated fatty acids (LCPUFAs) in EAU (76). Histological analysis at 17 days after disease induction revealed retinal folds and immune cell infiltration in the eyes of EAU mice that received DCs from ω-6 LCPUFA-fed mice, and showed that such changes were markedly suppressed in EAU mice that received DCs from ω-3 LCPUFA-fed mice ( Figure 1A) (77). Furthermore, DCs exposed to ω-3 LCPUFAs in vivo or in vitro suppressed T cell proliferation.…”
Section: Dendritic Cells In Eaumentioning
confidence: 99%
“…* P < 0.05, *** P < 0.001; NS, not significant vs. the corresponding value for the ω-6 LCPUFA diet (i.e., Sidak's multiple comparison test). The figure is reproduced from ( 77 ) with permission.…”
Section: Non-infectious Uveitis (Niu)mentioning
confidence: 99%